DETERMINATION OF IBUPROFEN AND 1-HYDROXYIBUPROFEN IN AQUEOUS SAMPLES USING CORK AS A NATURAL PHASE IN ROTATING-DISK SORPTIVE EXTRACTION - Richter, Pablo (Journal of the Chilean Chemical Society, 2023)
Ibuprofen is one of the most widely used nonsteroidal anti-inflammatory drugs due to its analgesic, anti-inflammatory and antipyretic properties, as well as its low cost and easy accessibility. A fraction of the compound and its metabolites are excreted in the urine, being eliminated in the wastewater reaching river waters in the range of ng L-1 to µg L-1. In this context, highly sensitive and selective analytical methods are required to quantify them, including these methods a pre-concentration step. In this work, the use of a microextraction technology based on rotating-disk sorptive extraction, involving a sorptive phase of laminar cork, was implemented for the extraction of ibuprofen and 1-hydroxyibuprofen from aqueous samples and their subsequent determination by gas chromatography coupled to mass spectrometry. The optimal conditions for determination of the analytes were: 20 mL of sample volume, pH 2, 20 % w/v NaCl (to increase the ionic strength), 90 min of extraction time and 2000 rpm of rotation velocity of the disk. Recoveries of 118 and 39 % and relative standard deviations of 6 and 13 % for ibuprofen and 1-hydroxyibuprofen were obtained, respectively. The presence of both compounds in river waters (Mapocho River, Santiago de Chile) at a concentration of 2.56 to 4.08 µg L-1 were found. The use of laminar cork as a natural sorbent phase immobilized in the rotating-disk allowed to extract the analytes from water samples through its lipophilic-hydrophilic balance that favors the interaction with the compounds under study.